Amikacin Liposome Inhalation Suspension (ALIS) Penetrates Non-tuberculous Mycobacterial Biofilms and Enhances Amikacin Uptake Into Macrophages - Zhang, Jimin; Leifer, Franziska; Rose, Sasha; Chun, Dung Yu; Thaisz, Jill; Herr, Tracey; Nashed, Mary; Joseph, Jayanthi; Perkins, Walter R.; DiPetrillo, Keith (Frontiers in Microbiology, 2018)
Nontuberculous mycobacteria (NTM) cause pulmonary infections in patients with structural lung damage, impaired immunity, or other risk factors. Delivering antibiotics to the sites of these infections is a major hurdle of therapy because pulmonary NTM infections can persist in biofilms or as intracellular infections within macrophages. Inhaled treatments can improve antibiotic delivery into the lungs, but efficient nebulization delivery, distribution throughout the lungs, and penetration into biofilms and macrophages are considerable challenges for this approach. Therefore, we developed amikacin liposome inhalation suspension (ALIS) to overcome these challenges. Nebulization of ALIS has been shown to provide particles within the respirable size range that distribute to both central and peripheral lung compartments in humans. The in vitro and in vivo efficacy of ALIS against NTM have been demonstrated previously. The key mechanistic questions are whether ALIS penetrates NTM biofilms and enhances amikacin uptake into macrophages. We found that ALIS effectively penetrated throughout NTM biofilms and concentration-dependently reduced the number of viable mycobacteria. Additionally, we found that ALIS improved amikacin uptake by ~4-fold into cultured macrophages compared with free amikacin. In rats, inhaled ALIS increased amikacin concentrations in pulmonary macrophages by 5–8 fold at 2, 6, and 24 hr post-dose and retained more amikacin at 24 hr in airways and lung tissue relative to inhaled free amikacin. Compared to intravenous free amikacin, a standard-of-care therapy for refractory and severe NTM lung disease, ALIS increased the mean area under the concentration-time curve in lung tissue, airways, and macrophages by 42-, 69-, and 274-fold. These data demonstrate that ALIS effectively penetrates NTM biofilms, enhances amikacin uptake into macrophages, both in vitro and in vivo, and retains amikacin within airways and lung tissue. An ongoing Phase III trial, adding ALIS to guideline based therapy, met its primary endpoint of culture conversion by month 6. ALIS represents a promising new treatment approach for patients with refractory NTM lung disease.